Design and Implementation of a RESTful API-Based Point of Sale System - Fulandi Hudza Grahitama; Waskitho Cito Adiwiguno; Syafrial Fachri Pane (NUANSA INFORMATIKA, 2025)
Point of Sale (POS) systems are essential for modern businesses, streamlining transactions, inventory management, and customer interactions. However, traditional POS systems face challenges such as limited real-time data processing, scalability issues, and restricted integration capabilities. This study proposes a RESTful API-based POS system using Supabase and Express.js to overcome these limitations.The system is developed using a hybrid waterfall methodology, combining structured phases with iterative refinement, and employs a relational database normalized to the third normal form (3NF) for data integrity and scalability. Supabase, as a backend-as-a-service platform, simplifies backend operations with its robust features for database management, authentication, and real-time APIs. Meanwhile, Express.js provides a lightweight and efficient framework for developing RESTful APIs, ensuring seamless integration and efficient data handling. Comprehensive testing, including black box testing, confirms the system’s reliability, ensuring its readiness for real-world implementation. The results highlight the system’s ability to enhance operational efficiency and adapt to dynamic business requirements. This study demonstrates how integrating RESTful APIs, Supabase, and Express.js can modernize POS systems, providing scalable, secure, and efficient solutions tailored to the demands of a data-driven marketplace.